2019
DOI: 10.1167/iovs.19-27028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Retinal Microvasculature in Patients With Alzheimer's Disease and Primary Open-Angle Glaucoma by Optical Coherence Tomography Angiography

Abstract: PURPOSE. Comparison of retinal microvasculature within the macula and the optic nerve head in the eyes of patients with Alzheimer's disease (AD), primary open-angle glaucoma (POAG), and in a healthy control (HC) group, using optical coherence tomography angiography (OCTA). METHODS. In this cross-sectional study, 27 patients with AD, 27 with POAG, and 27 healthy controls were enrolled. The Mini-Mental State Examination test was used to assess cognitive function. Ophthalmic examination included OCTA, which was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(133 citation statements)
references
References 43 publications
5
120
0
1
Order By: Relevance
“…This is contrary to what has been observed in human vessel microangiography studies. 22,23 However, in the previous human studies, the area of interest usually targets the fovea. Since mice do not have a fovea, there is not an equivalent measurement in the mouse retina.…”
Section: Cortical Amyloid Beta Plaque Loadmentioning
confidence: 99%
“…This is contrary to what has been observed in human vessel microangiography studies. 22,23 However, in the previous human studies, the area of interest usually targets the fovea. Since mice do not have a fovea, there is not an equivalent measurement in the mouse retina.…”
Section: Cortical Amyloid Beta Plaque Loadmentioning
confidence: 99%
“…[10] While there are a few OCTA studies investigating AD, there have been mixed conclusions. [11][12][13][14][15] Some researchers reported nding signi cant reduction in the vessel density (VD) only in the super cial plexus, [14,16] which complements histology ndings [10] and OCT studies [9] since the super cial plexus mainly supplies the inner retinal layer. [17] However, others reported nding changes only in the deep plexus.…”
Section: Introductionmentioning
confidence: 59%
“…Four OCTA studies have investigated DCP VD in AD individuals, but there is generally a lack of agreement between studies (Table 4). Two studies [11,15] showed a signi cant reduction in VD in AD individuals whereas the others [14,16] did not observe any differences. Obtaining accurate OCTA metrics from the DCP layer is particularly challenging as it is affected by the physiologic variability of FAZ [18,19] and projection artefacts.…”
Section: Dcp In Ad Individualsmentioning
confidence: 92%
See 2 more Smart Citations